The educational role of the family in building the attitudes of choosing the future profession of its students (A field study in Baghdad / Al-Karkh center) (Journal of the College of Basic Education, 2022)
Young youth(Two work sincerely so that you are aware of them and do not envy you, the mother and the father)The researcher wanted to know the attitudes of an important and wide segment of society represented by the segment (students) in the preparatory stage towards their choice of the future profession as an influential segment in the building and development of the country, so the current research aims to know the following:1- Knowing the first influencing factor in building the attitudes of the future profession of children (students).2- Knowing the first influencing factor in building parents' future career trends.3- Knowing the significance of statistical differences in building students' future profession trends.4- Knowing the significance of statistical differences in building parents' future career trends.